The Rights Of Children Over A Deceased Parent Matrimonial Property; Special Reference To Family Business - Zuhairah Ariff, Abd Ghadas; Norliah, Ibrahim (2017)
A couple of years ago, the country was stirred by the legal suits taken by eleven siblings against their estranged father over their inheritance and their deceased mother's matrimonial property (Khalilullah Che Ibrahim and Ors v Che Ibrahim Che Ismail, Syariah High Court, Kota Bharu , Kelantan). The children succeeded in their application for an ex parte interim order to restrain their father from entering into any form of transaction on the claimed property. The law suit is expected to be in the millions as it involves numerous properties and shares belonging to the defendant. This paper discusses issues relating to rights of children to claim a deceased parent interest in matrimonial property by way of legal analysis. Research methodologies applied in this paper are statutory and doctrinal analysis.